Economic Development as a matter of political geography - Streb, Jorge (Estudios de Economía, 2016)
Can limited government be a driving force of economic development? This ideagoes back to Montesquieu, and is closely related to recent research in institutionaleconomics. Measuring limited government with the Henisz political constraintsindex, and economic development with income per capita, the paper first does acausality test to see whether political constraints lead income per capita. Sinceboth are persistent variables, their differences are analyzed. The evidence fromthe 1960-1990 period indeed suggests that increases in political constraintsprecede economic growth. The effect of political constraints might take a longtime period to set in, so a second test looks at the link between income percapita and polity persistence, conditioned on the degree of political constraints.Polity persistence is positively linked to income per capita with high politicalconstraints, but there is no link with low political constraints. This broaderevidence suggests that limited government has been conducive to economicdevelopment over the long run.